The Efficacy of Monoplant® and Indoplant® as Contraceptive Methods: A Comparative Study - Gunardi, Eka R; Ballo, Frista (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the effectiveness, safety, and time of insertion between Monoplant® with Indoplant® to prevent pregnancy. Methods: Data were collected from November 2015 until May 2016 in Raden Saleh Clinic. A total of 153 patients met the inclusion and exclusion criteria for the study and were divided into 77 patients who received Monoplant® and 76 patients received Indoplant®. The study period was 6 months. Results: The data obtained showed no significant difference in the effectiveness of both contraceptive methods. In addition, side effects such as menstrual disorders and weight gain did not differ significantly in those study groups. However, the time of insertion between Monoplant® and Indoplant® was siginificantly different (162.91 + 197.04 + 49.81 seconds versus 44.96 seconds, p<0.001). For complications such as skin irritation, inflammation, there are no differences between Monoplant® (0.0%) and Indoplant® users (0.0%). Conclusion: There are no significant differences in efficacy and side effects using Monoplant® and Indoplant® during the 6-month follow-up. However, the insertion time of Monoplant® is shorter compared to Indoplant®’s. Monoplant® can be considered for use as contraception with the effectiveness and side effects are almost the same, but with shorter time of insertion compared to Indoplant ®. [Indones J Obstet Gynecol 2017; 5-2: 94-98] Keywords: contraception, implant, indoplant®, monoplant®